ХАРАКТЕРИСТИКА ЗООБЕНТОСА ЛИГУРИЙСКОГО МОРЯ - (:unkn) unknown (Киев : Наукова думка, 1983)
Представлены результаты исследования макро- и мейобентоса в различных биотопах Лигурийского моря на глубинах 115—640 м. Средняя численность макрозообентоса 233 экз/м2, биомасса 21,0 г/м2. Биотопы литотамния и крупнозернистого песка с битой ракушей наиболее благоприятны для развития макрофауны (соответственно 767 экз/м2 и 76,7 г/м2, 127 экз/м2 и 22,0 г/м2). Биотоп пелитового ила характеризуется самыми низкими численностью и биомассой макробентоса (58 экз/м2 и 0,99 г/м2). Численность мейобентоса 5802 экз/м2, биомасса 0,122 г/м2. Нематоды и полихеты — доминирующие группы мейобентоса. Наибольшая плотность поселения организмов отмечена в биотопах мелкого песка, литотамния и алевритового ила (7539—7968 экз/м2). В биотопе крупнозернистого песка численность мейофауны вдвое меньше, а в биотопе пелитового ила — втрое. Определено количественное соотношение макро- и мейобентоса в различных биотопах. Для исследованного района моря соотношение численности макро- и мейобентоса 1:25, биомасс — 172:1.
Characterization of zoobenthos of the Ligurian Sea
Sampling was made in, May of 1974, and in the studied region of the Ligurian Sea at a 115—640 m depth five biotopes were distinguished: coarse and fine sands, lythothamnium, aleuritic and pelitic muds. Various biotopes were analyzed for systematic composition and quantitative distribution of macrozoobenthos. Biotopes of lithothamnium and coarse sand are found to have the highest indices of macrobenthos number and biomass (767 specimen/m2; 76.7 g/m2 and 127 specimen/m2; 22.0 g/m2, respectively). The pelitic mud biotope is featured by a small number (58 specimen/m2) and biomass (0.99 g/m2). Average numbers of macrobenthos in the region under study are 233 specimen/m2 with average biomass 21.0 g/m2. The number of meiofauna is 25 times as high as that of macrobenthos. Its average amount is 5802 specimen/m2, biomass — 0.122 g/m2. Free-living nematodes and Polychaeta are dominating meiofauna groups. Biotopes of fine sand, lithothamnium and aleuritic mud contain almost equal amounts of meiobenthos (7539-7968 specimen/m2) with biomass being 0.091, 0.253 and 0.127 g/m2, respectively. Meiobenthos number in the coarse sand biotope is twice lower and in the pelitic mud biotope — thrice as. low as those previously mentioned.